Phase transitions in strongly interacting quantum field theories: QED_3 vs. QCD - Bonnet, Jacqueline A.; Justus Liebig University Giessen (My University, 2013)
In this thesis, we investigate strongly coupled quantum field theories on the examples of (2+1) dimensional Quantumelectrodynamics (QED_3) and (3+1) dimensional Quantum Chromodynamics (QCD) in the framework of Dyson-Schwinger equations. We firstly focus on the chiral phase transition in QED_3 as a low-energy effective theory for high-temperature superconductors. These materials are inherently anisotropic, as shown by experiments. We therefore focus on the influence of an anisotropic spacetime onto the critical number of fermion flavors for chiral symmetry breaking at zero and finite temperature. The findings are summarized in phase diagrams for the critical number of fermion flavors as a function of the independent anisotropic velocities and temperature. These were the first calculations considering anisotropic QED_3 at finite temperatures. Furthermore, the presented investigations elaborate on the critical scaling behavior close to the merging region of the thermal phase transition line and the quantum phase transition point. The most important results include the finding that anisotropy provides an external parameter that determines the scaling scenario. Secondly, the QCD part of this thesis consists of a feasibility study of the implementation of external magnetic fields into the Dyson-Schwinger formalism. This study serves as a basis for further investigations of e.g. the dynamical mass generation at finite temperatures and densities. This will allow to contribute to the discussions on the phenomenon of (inverse) magnetic catalysis from a functional methods´ point of view. Furthermore, we present the first successful extraction of a dressed Wilson loop from Dyson- Schwinger equations. It represents an observable for confinement that was recently introduced in the framework of lattice gauge theory. In addition, its connection with the conventional Wilson loop allows for a direct extraction of the string tension.

In dieser Arbeit werden stark gekoppelte Quantenfeldtheorien an Hand der Beispiele der Quantenelektro-dynamik in (2+1) Dimensionen (QED_3) und der Quantenchromodynamik (QCD) im Rahmen der Dyson-Schwinger Methode untersucht. Zuerst analysieren wir hierbei den chiralen Phasenübergang der QED_3 als eine effektive Niederenergietheorie für Hochtemperatursupraleiter. Experimentell wurde gefunden, dass diese Materialien inhärent anisotrop sind. Daher betrachten wir den Einfluss einer anisotropen Raumzeit auf die kritische Zahl der Fermionenflavors für chirale Symmetriebrechung bei verschwindender und endlicher Temperatur. Die Ergebnisse sind in Phasendiagrammen für die kritische Anzahl an Fermionenflavors als Funktion unabhängiger anisotroper Geschwindigkeiten und der Temperatur zusammengefasst. Diese Untersuchungen sind die Ersten, die anisotrope QED_3 bei endlichen Temperaturen betrachten. Desweiteren beschäftigt sich die vorliegende Arbeit mit dem kritischen Skalierungsverhalten nahe des Übergangs der thermischen Phasenübergangslinie in den Quantenphasenübergangspunkt. Die wichtigsten Resultate dieser Untersuchung sind hierbei, dass die Anisotropie einen externen Parameter darstellt, der das Skalierungsverhalten bestimmt. Der zweite, QCD bezogene Teil dieser Arbeit enthält eine Machbarkeitsstudie über die Implementierung externer Magnetfelder im Dyson-Schwinger Formalismus. Diese Studie dient als Ausgangspunkt für weitere Untersuchungen z.B. der dynamischen Massenerzeugung bei endlichen Temperaturen und Dichten. Diese werden es ermöglichen zu aktuellen Diskussionen bezüglich des Phänomens der (inversen) magentischen Katalyse aus der Sicht funktionaler Methoden beitragen zu können. Desweiteren präsentiert die vorliegende Arbeit die erste erfolgreiche Berechnung gedresster Wilsonloops mit Hilfe der Dyson-Schwinger Gleichungen. Dieser stellt eine Observable für Confinement dar, die kürzlich im Rahmen der Gittereichtheorie eingeführt wurde. Zusätzlich erlaubt die Verbindung zum konventionellen Wilsonloop eine direkte Extraktion der Stringtension.
Phasenübergänge in stark wechselwirkenden Quantenfeldtheorien: QED_3 vs. QCD
Keywords: QED_3; Dyson-Schwinger Gleichungen; Chirale Symmetriebrechung; QCD; Confinement; QED_3; Dyson-Schwinger equations; chiral symmetry breaking; QCD; confinement; ddc:530